1998
DOI: 10.1176/ajp.155.11.1608
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in Mania: A Controlled Study

Abstract: The therapeutic effect of transcranial magnetic stimulation in mania may show laterality opposite to its effect in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(70 citation statements)
references
References 9 publications
3
62
1
4
Order By: Relevance
“…Also, functional magnetic resonance activation during an n-back task where subjects had to identify letters two positions back in a letter sequence, replicated prior findings of bilateral dorsolateral prefrontal cortex and parietal regions in healthy controls, whereas BD patients revealed reduced right parietal activation (Townsend et al, 2010). Moreover, a study (Grisaru et al, 1998) investigated the clinical properties of repetitive transcranial magnetic stimulation applied over the left and right prefrontal cortex. The results showed that manic symptoms of BD patients significantly improved after repetitive transcranial magnetic stimulation over the right prefrontal cortex compared to BD patients receiving repetitive transcranial magnetic stimulation of the left prefrontal cortex.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Also, functional magnetic resonance activation during an n-back task where subjects had to identify letters two positions back in a letter sequence, replicated prior findings of bilateral dorsolateral prefrontal cortex and parietal regions in healthy controls, whereas BD patients revealed reduced right parietal activation (Townsend et al, 2010). Moreover, a study (Grisaru et al, 1998) investigated the clinical properties of repetitive transcranial magnetic stimulation applied over the left and right prefrontal cortex. The results showed that manic symptoms of BD patients significantly improved after repetitive transcranial magnetic stimulation over the right prefrontal cortex compared to BD patients receiving repetitive transcranial magnetic stimulation of the left prefrontal cortex.…”
Section: Introductionsupporting
confidence: 72%
“…However, a right hemisphere involvement in BD has been suggested by findings of decreased gray matter volume in right prefrontal and parietal lobes (Lyoo et al, 2004;Adler et al, 2005) as well as cortical thinning in right superior parietal areas (Lyoo et al, 2006). In addition, neuroimaging and neurophysiological studies revealed atypical functional brain organization, particularly involving the right hemisphere rather than the left (e.g., Grisaru et al, 1998;Rubinsztein et al, 2001;Townsend et al, 2010). For example, a positron emission tomography study using a decision-making task, where participants were asked to choose between a red and a blue box to find a token, showed a decreased right superior frontal activation in manic BD patients compared to healthy controls (Rubinsztein et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A reversed pattern of lateralization in a subset of patients could explain why some patients paradoxically do better with an inhibitory stimulus to the left prefrontal cortex and worse with an excitatory one (52,54). The success of Grisaru's group in treating mania with high-frequency rTMS to the right prefrontal cortex complements this model (60).…”
Section: Pulse Frequency-slow Versus Fast Rtmsmentioning
confidence: 95%
“…In the last two decades, research on using these tools to treat conditions such as depression 6 , mania 7 , obsessive-compulsive disorder 8 and post-traumatic stress disorder 9 began to appear. The use of electric currents for treating psychiatric disorders began in the 18 th century with the development of the voltaic pile.…”
mentioning
confidence: 99%